Difference between revisions of "022 Exam 2 Sample A, Problem 1"

From Math Wiki
Jump to navigation Jump to search
Line 15: Line 15:
 
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>(fg)'(x) = f'(x)\cdot g(x)+f(x)\cdot g'(x).</math>
 
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>(fg)'(x) = f'(x)\cdot g(x)+f(x)\cdot g'(x).</math>
 
|-
 
|-
|<br>'''The Quotient Rule:'''  If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions and <math style="vertical-align: -21%;">g(x) \neq 0</math>&thinsp;, then
+
|<br>'''The Quotient Rule:'''  If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -20%;">g</math> are differentiable functions and <math style="vertical-align: -21%;">g(x) \neq 0</math>&thinsp;, then
 
|-
 
|-
 
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>\left(\frac{f}{g}\right)'(x) = \frac{f'(x)\cdot g(x)-f(x)\cdot g'(x)}{\left(g(x)\right)^2}. </math>
 
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>\left(\frac{f}{g}\right)'(x) = \frac{f'(x)\cdot g(x)-f(x)\cdot g'(x)}{\left(g(x)\right)^2}. </math>
Line 32: Line 32:
 
::<math>f(x)\,=\,\frac{(x+5)(x-1)}{x},</math>
 
::<math>f(x)\,=\,\frac{(x+5)(x-1)}{x},</math>
 
|-
 
|-
|we then have <math style="vertical-align: -21%">y\,=\,g\circ f(x)\,=\,g\left(f(x)\right).</math>
+
|we then have&thinsp; <math style="vertical-align: -21%">y\,=\,g\circ f(x)\,=\,g\left(f(x)\right).</math>
 
|}
 
|}
  
Line 38: Line 38:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|We can now apply all three advanced techniques.  For example, to find the derivative <math>f'(x)</math>,
+
|We can now apply all three advanced techniques.  For <math style="vertical-align: -20%">f'(x)</math>, we must use both the quotient and product rule to find
 +
|-
 +
|<br>
 +
::<math>\begin{array}{rcl}
 +
f'(x) & = & \displaystyle{\frac{\left((x+5)(x-1)\right)'x-(x+5)(x-1)(x)'}{x^{2}}}\\
 +
\\
 +
& = &  \displaystyle{\frac{\left[x^{2}+4x-5\right]'x-(x^{2}+4x-5)(x)'}{x^{2}}}\\
 +
\\
 +
& = &  \displaystyle{\frac{(2x+5)x-(x^{2}+4x-5)(1)}{x^{2}}}\\
 +
\\
 +
& = &  \displaystyle{\frac{2x^{2}-5x-x^{2}-4x+5}{x^{2}}}\\
 +
\\
 +
& = &  \displaystyle{\frac{x^{2}-9x+5}{x^{2}}}.
 +
\end{array}</math>
 
|
 
|
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Part (c): &nbsp;
+
!Step 3: &nbsp;
 
|-
 
|-
|We can choose to expand the second term, finding
+
|We can now use the chain rule to find<br>
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; &nbsp; <math>e(x^{2}+2)^{2}=ex^{4}+4ex^{2}+4e.</math>
+
|
 +
::<math>\begin{array}{rcl}
 +
y' & = & \left(g\circ f\right)'(x)\\
 +
\\
 +
& = & g'\left(f(x)\right)\cdot f'(x)\\
 +
\\& = & \displaystyle{\frac{x}{(x+5)(x-1)}\cdot\frac{x^{2}-9x+5}{x^{2}}}\\
 +
\\
 +
& = & \displaystyle{\frac{x^{2}-9x+5}{x^{3}+4x^{2}-5x}.}
 +
\end{array}</math>
 +
Note that many teachers <u>'''do not'''</u> prefer a cleaned up answer, and may request that you <u>'''do not simplify'''</u>.  In this case, we could write the answer as<br>  
 
|-
 
|-
|We then only require the product rule on the first term, so
+
|
 +
::<math>y'=\displaystyle {\frac{x}{(x+5)(x-1)}\cdot\frac{(2x+5)x-(x^{2}+4x-5)(1)}{x^{2}}.}</math>
 +
 
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Final Answer: &nbsp;
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; &nbsp; <math>h'(x)\,=\,(4x)'\cdot\sin(x)+4x\cdot(\sin(x))'+\left(ex^{4}+4ex^{2}+4e\right)'\,=\,4\sin(x)+4x\cos(x)+4ex^{3}+8ex.</math>
+
|<math>y'\,=\,\displaystyle{\frac{x^{2}-9x+5}{x^{3}+4x^{2}-5x}.}</math>
 
|}
 
|}
  
 
[[022_Exam_2_Sample_A|'''<u>Return to Sample Exam</u>''']]
 
[[022_Exam_2_Sample_A|'''<u>Return to Sample Exam</u>''']]

Revision as of 14:47, 14 May 2015

Find the derivative of  

Foundations:  
This problem requires several advanced rules of differentiation. In particular, you need
The Chain Rule: If and are differentiable functions, then

    

The Product Rule: If and are differentiable functions, then

    

The Quotient Rule: If and are differentiable functions and  , then

    

 Solution:

Step 1:  
We need to identify the composed functions in order to apply the chain rule. Note that if we set , and
we then have 
Step 2:  
We can now apply all three advanced techniques. For , we must use both the quotient and product rule to find

Step 3:  
We can now use the chain rule to find

Note that many teachers do not prefer a cleaned up answer, and may request that you do not simplify. In this case, we could write the answer as

Final Answer:  

Return to Sample Exam